Taxonomic Revision, Morphology and Natural History of the Stick Insect Genus Xerosoma Serville, 1831 (Insecta: Phasmatodea) - Engelking, Phillip Watzke [UNESP]; Ghirotto, Victor Morais; Crispino, Edgar Blois; Büscher, Thies H.; Heleodoro, Raphael Aquino; Neves, Pedro Alvaro Barbosa Aguiar; Bispo, Pitágoras da Conceição [UNESP] (My University, 2023)
Stick insects (Phasmatodea) are quite diverse in the Neotropical region. Among them, Xerosoma Serville belongs to Pseudophasmatidae and comprises winged, roughly brownish phasmids that resemble bark or dry branches and inhabit the Atlantic Forest in Brazil. In this study, we present a redescription and revision of the genus that include three valid species, Xerosoma canaliculatum, Xerosoma michaelis, and Xerosoma nannospinus sp. nov. Xerosoma senticosum syn. nov. was found to be a junior synonym of X. canaliculatum. We also provide an identification key and geographic records for these three species. Additionally, we present a detailed study on the morphology and natural history of X. canaliculatum with the description of its nymphal stages, egg, male genitalia, ontogeny, oviposition method, life habits, defense mechanisms, mating behavior, and other aspects regarding its biology. The study also highlights the shortcomings related to the classification of Xerosomatinae, since its tribes find themselves without proper characterization and contain heterogeneous genera. We expect to provide a basis for a proper diagnosis of Xerosomatinae and encourage future studies on this group, as there is still much to be discovered about this lineage of Neotropical stick insects.
Keywords: Animal behavior; Atlantic Forest; Brazilian fauna; Mating behavior; Taxonomy